The Influence of Game-Based Learning Assisted by Wordwall on Informatics Learning Outcomes - Raihan Bima Agwicahya; Basori basori; Agus Efendi (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2025)
The research was conducted with the aim of knowing the difference in the effect of the application of game-based learning assisted by Wordwall on the learning outcomes of the informatics class VII SMP Negeri 3 Colomadu. The design of this research is a quasi-experiment. The population used was all seventh-grade students of SMP Negeri 3 Colomadu. The sampling technique used was cluster random sampling, so that the samples used were 32 students from class VII A as the experimental class group and 32 students from class VII B as the control class group. The technique used is by giving tests which include a pretest and a posttest. Prerequisite test by doing the normality test with the Kolmogorov-Smirnov and the homogeneity test with Levene. Data analysis is by independent sample t-test and paired sample t-test with a significant value limit of 0.05 and N-Gain Score, with the help of the SPSS 25 application program. The results obtained show that there is an influence on the application of game- based learning aided by Wordwall on the learning outcomes of the informatics class VII SMP Negeri 3 Colomadu. It can be seen from the calculation of the independent sample t-test, which shows a significance value of 0.036 <0.05, and the paired sample t-test results show a value of 0.000 <0.05. These results show that the use of game-based learning assisted by Wordwall has an effect on learning outcomes. The results on the N-Gain Score also show that the score obtained by the experimental group is higher than the control group, namely 0.4212 > 0.1630. From these results, the experimental group obtained a score that is moderate. These findings suggest that digitally gamified review platforms can serve as effective pedagogical supplements in technology-integrated classrooms, warranting further investigation across diverse subject areas and school contexts.